Affinity-bound growth factor within sulfated interpenetrating network bioinks for bioprinting cartilaginous tissues - Kelly, Daniel (My University, 2021)
3D bioprinting has emerged as a promising technology in the field of tissue engineering and regenerative medicine due to its ability to create anatomically complex tissue substitutes. However, it still remains challenging to develop bioactive bioinks that provide appropriate and permissive environments to in- struct and guide the regenerative process in vitro and in vivo. In this study alginate sulfate, a sulfated glycosaminoglycan (sGAG) mimic, was used to functionalize an alginate-gelatin methacryloyl (GelMA) in- terpenetrating network (IPN) bioink to enable the bioprinting of cartilaginous tissues. The inclusion of alginate sulfate had a limited influence on the viscosity, shear-thinning and thixotropic properties of the IPN bioink, enabling high-fidelity bioprinting and supporting mesenchymal stem cell (MSC) viability post- printing. The stiffness of printed IPN constructs greatly exceeded that achieved by printing alginate or GelMA alone, while maintaining resilience and toughness. Furthermore, given the high affinity of algi- nate sulfate to heparin-binding growth factors, the sulfated IPN bioink supported the sustained release of transforming growth factor-β3 (TGF-β3), providing an environment that supported robust chondroge- nesis in vitro, with little evidence of hypertrophy or mineralization over extended culture periods. Such bioprinted constructs also supported chondrogenesis in vivo, with the controlled release of TGF-β3 pro- moting significantly higher levels of cartilage-specific extracellular matrix deposition. Altogether, these results demonstrate the potential of bioprinting sulfated bioinks as part of a ‘single-stage’ or ‘point-of- care’ strategy for regenerating cartilaginous tissues
Keywords: 3D bioprinting; Bioinks; tissue substitutes; 3D bioprinting; Bioinks; tissue substitutes